Leveling Buku, Jurnal Membaca dan Maker Space: Ekosistem Literasi di Sekolah Dasar - Prasetyaningtyas, Hariyani; Sofwan, Muhammad; Sugiarto, Sugiarto; Takdir, Muhammad; Syam, Aldo Redho; Mayasari, Linda Ika (Proceeding of Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
Strengthening literacy in primary schools in the era of Society 5.0 requires management that goes beyond reading habituation and emphasizes the development of an integrated and sustainable literacy ecosystem. This study aims to map the initial configuration of literacy management at SD Gagas Ceria Bandung through a grand tour exploration, focusing on book leveling practices, reading journals, and the utilization of maker spaces as integral components of the school literacy ecosystem. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, classroom and maker space observations, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that literacy management has developed organically and systemically through daily reading routines, a mandatory reading policy of 20 books per year, a structured book leveling system, and the use of reading journals as authentic assessment tools. Teachers serve as the primary drivers of literacy practices, supported by the school library in providing and rotating collections, while maker spaces extend literacy practices toward multiliteracies. The main challenges identified include limited availability of book copies, the complexity of maintaining consistent leveling, and instances of plagiarism in reading summaries. Overall, the study concludes that the literacy ecosystem at SD Gagas Ceria is well-established and relatively stable despite the absence of a national literacy syllabus, thereby providing a strong empirical foundation for the development of context-based literacy management models and for more in-depth future research.